Institutional Analysis of Sustainable Management of the Sekampung Watershed, Lampung Province, Indonesia - Edison; Banuwa, Irwan Sukri; Yuwono, Slamet Budi; Damai, Abdullah Aman; Hidayat, Kuswanta Futas; Suroso, Erdi; Hasani, Qadar (Jurnal Sylva Lestari, 2025)
The Sekampung Watershed is one of the 108 critical national watersheds designated by the government as requiring restoration of its carrying capacity. In addition to restoration challenges, a lack of coordination among various institutions has led to fragmented and uncoordinated efforts in watershed conservation. Addressing these, researching the institutional aspects of sustainable management by synergistic governance across sectors in the Sekampung watershed is crucial. This study aimed to determine the key institutions directly involved in the sustainable management of the Sekampung Watershed in Lampung Province, along with their coordination mechanisms and interrelationships. This study also aimed to identify constraints in the sustainable management implementation of the Sekampung watershed. The study employed the Interpretative Structural Modelling (ISM) method using questionnaires and expert discussions. The results show that the key institutions in the integrated management of the watershed to ensure the Sekampung Watershed’s functions are preserved and sustainably utilized were the provincial government institutions, governor, regent, mayor, together with the Provincial and Regency or City Regional House of Representatives (DPRD), the Bukit Barisan Selatan National Park Authority (BBTNBBS), and the Way Seputih Way Sekampung Watershed and Forest Management Agency (BPDAS HL WSS). The low awareness care of the community towards watershed management was identified as a critical constraint that must be addressed for the successful sustainable management of the Way Sekampung Watershed. Keywords: institutional analysis, interpretative structural modelling, protected forest, Sekampung Watershed, stakeholder